Dr. Neal Barnard's cookbook for reversing diabetes : 150 recipes scientifically proven to reverse diabetes without drugs - Barnard, Neal D., 1953-; Burton, Dreena, 1970- (Rodale Press, 2018)
Finally an approach to managing diabetes that is not based on pills or injections, but on food--the most delicious "prescription" you could imagine. Written by Dr. Neal Barnard, the unparalleled expert on diabetes and health, with recipes developed by Dreena Burton, bestselling cookbook author and creator of the Plant Powered Kitchen blog, this plant-based cookbook is filled with 150 easy and delicious recipes. Inside, expect to find favorite foods like burgers, onion rings, muffins, and pudding, but approached from a healthful angle--focusing on vegetables, fruits, whole grains, and legumes. Dr. Barnard also offers thorough explanations about the scientific relationship between nutrition and diabetes, and identifies the ingredients in the book by their vitamins, nutritional properties, and health power in a simple and easy to understand way. Dr. Neal Barnard's Cookbook for Reversing Diabetes is a treasury of meals that are as tasty as they are powerful for health.